Pengembangan Instrument Kuesioner Model Self Determinasi Pada Kebiasan Sarapan Pagi Remaja Di Sekolah Menegah Pertama - Hadjo, Samuel; Kasenda, Telvie; Hadjo, Nicely (Jurnal Sosial Teknologi, 2025)
This study aims to develop and validate a questionnaire instrument based on Self-Determination Theory to measure breakfast habits among junior high school adolescents. Breakfast is a crucial factor in supporting adolescents' physical and cognitive health, yet the underlying psychological motivations for this habit remain underexplored. Self-Determination Theory emphasizes three basic psychological needs—autonomy, competence, and relatedness—which are believed to contribute to intrinsic motivation in maintaining healthy behaviors, such as breakfast consumption. This research used an explanatory survey design with a cross-sectional approach. The sample consisted of 119 students from UNKLAB Junior High School, Airmadidi, North Minahasa, selected using stratified random sampling. The research instrument was a modified self-determination questionnaire adapted to the local context. Validity and reliability tests showed that the questionnaire had strong construct validity and reliability. This study contributes to the development of a measurement tool that can be utilized in adolescent health promotion and nutritional interventions. Further validation is recommended to improve the cultural and social sensitivity of the instrument.